THE IMPACT OF ARTIFICIAL INTELLIGENCE ON THE LABOR MARKET (Economics and region, 2024)
The development of artificial intelligence is having a significant impact on the modern labor market, transforming both individual industries and the economy as a whole. In Ukraine, this influence is especially important due to economic challenges and the need to quickly adapt to new conditions in the global market. The article analyzes the impact of artificial intelligence on the Ukrainian labor market, taking into account global trends and local peculiarities. The article uses methods of comparative analysis, statistical analysis and expert evaluation. Data from international sources, including Statista and International Monetary Fund reports, are used for the analysis. The analysis shows that the artificial intelligence market is growing rapidly, driven by the introduction of technologies in various sectors. The global artificial intelligence market is projected to exceed USD 826 billion in 2030, which will have a significant impact on the labor market. In Ukraine, artificial intelligence creates new opportunities, but also brings challenges, such as job replacement and the need for new skills. The Global Artificial Intelligence Index for 2024 reflects a fairly high position of Ukraine (26th out of 138), which indicates the need to improve artificial intelligence governance, its ethical development, and compliance with international standards. The results presented in this article can be used to develop strategies for adapting Ukraine's labor market to new realities, including training for new professions, investment in education, and support for innovative entrepreneurship. The conclusions state that artificial intelligence has significant potential to increase productivity and create new jobs in high-tech sectors, but also carries the risk of reducing employment in traditional industries. To maximize the potential of artificial intelligence, comprehensive strategies are needed to train employees, develop new skills, and create ethical standards for the use of artificial intelligence. This approach will contribute to the balanced and sustainable development of Ukraine's labor market in the context of digital transformation.
Keywords: artificial intelligence; labor market; automation; digital transformation; smart business; regional economy; entrepreneurship; usiness culture; global economy